2013
DOI: 10.1200/jco.2013.31.26_suppl.12
|View full text |Cite
|
Sign up to set email alerts
|

L-Dex ratio in detecting and diagnosing breast cancer-related lymphedema: Reliability, sensitivity, and specificity.

Abstract: Advances in bioelectrical impedance analysis (BIA) permit the assessment of lymphedema by directly measuring lymph fluid changes. The purpose of the study was to examine the reliability, sensitivity, and specificity of cross-sectional assessment of BIA in detecting lymphedema in a large metropolitan clinical setting. BIA was used to measure lymph fluid changes. Limb volume by sequential circumferential tape measurement was used to validate the presence of lymphedema. Data were collected from 250 women, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
135
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(140 citation statements)
references
References 21 publications
4
135
1
Order By: Relevance
“…These measures are compared with previously established baseline measures or normative standards for quantifying lymphedema. Normal L-Dex scores lie between −10 and +10, which is equivalent to an impedance ratio range of 0.935 to 1.139 for at-risk dominant arms and 0.862 to 1.006 for at-risk nondominant arms, calculated as 3 standard deviations from the mean normative data 41. Scores outside this range are indicative of lymphedema.…”
Section: Bioimpedance Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These measures are compared with previously established baseline measures or normative standards for quantifying lymphedema. Normal L-Dex scores lie between −10 and +10, which is equivalent to an impedance ratio range of 0.935 to 1.139 for at-risk dominant arms and 0.862 to 1.006 for at-risk nondominant arms, calculated as 3 standard deviations from the mean normative data 41. Scores outside this range are indicative of lymphedema.…”
Section: Bioimpedance Analysismentioning
confidence: 99%
“…Newman et al45 found that BIA has the precision capable of detecting (1.65%-1.86%) the onset of extracellular fluid accumulation indicative of early development of lymphedema. Test-retest reliability using the Imp XCA analyzer, a clinical BIA device, demonstrates strong agreement in the healthy and at-risk groups (ICC = 0.99) but only fair agreement in the group with known breast cancer–related lymphedema (ICC = 0.69) 41. Concurrent validity has been studied using a variety of assessment methods involving both clinical and research models of BIA devices.…”
Section: Bioimpedance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These thresholds, like those derived for BIS [6], account for limb dominance and have been set at three standard deviations (3SD) above the mean of a control population. However, it has been suggested that the 3SD approach may be overly conservative [8,9]. Furthermore, which of these tools and thresholds best identify LE is unknown, as comparison against a reasonable reference standard has not been undertaken.…”
mentioning
confidence: 99%
“…12 The L-Dex ratio is reported as a standardized measure of the ratio of the impedance of extracellular water in the affected limb compared to the unaffected limb. 13 Qualitative and quantitative MRI measures of tissue structure MRI measurements were performed at 3 Tesla (Philips Medical Systems, Best, The Netherlands) using dual-channel body coil radiofrequency transmission and a 16-channel torso coil for reception. The qualitative structural MRI protocol was optimized in prior work 14 and consisted of custom diffusionweighted-inversion-with-background-suppression imaging for large axillary node identification (spatial resolution = 3 · 3 · 5 mm; b-value = 800 s/mm 2 ; TR/TE/TI = 7528/54/ 260 ms), T 1 -weighted multipoint DIXON (mDIXON) for tissue and node structure (3D-gradient-echo; TR = 3.4 ms; spatial resolution = 1.0 · 0.74 · 2.5 mm), high-spatial resolution fat-suppressed T 2 -weighted MRI for node structure visualization (turbo-spin-echo; TR = 3500 ms; TE = 60 ms; spatial resolution = 0.4 · 0.5 · 5 mm).…”
Section: Non-mri Measurementsmentioning
confidence: 99%